Static Spacer Construction Using Carbon Fiber Rods in 2-stage Revision for Periprosthetic Knee Infection: A Novel Technique and Indications. Issue 4 (December 2021) - Scott, Brandon; Levins, James; Mariorenzi, Michael; Marcaccio, Steven; Cohen, Eric
Abstract : Background: Traditionally, 2-stage exchange arthroplasty is preferred to eradicate chronic periprosthetic joint infections after total knee arthroplasty. However, for cases with significant bone destruction and/or soft tissue damage, the risk of knee instability increases with this technique, leading to a number of complications such as tibiofemoral dislocation, wound healing complications, extensor mechanism rupture, or failure of extensor mechanism repair. Intramedullary fixator rods reinforcing static spacers have been utilized to provide improved stability, but persistent infections were still prevalent. Antibiotic static spacers with intramedullary fixator rods coated with antibiotic cement can lower these reinfection rates. Surgical Technique: The surgical sequence requires removal of the infected prosthesis and placement of a carbon fiber rod and nonarticulating antibiotic spacer. This remains in situ for ~6 to 12 weeks while the patient receives systemic antibiotic treatment. Following confirmation of successful treatment, the antibiotic spacer and carbon fiber rod are removed, and revision arthroplasty is performed in a standard manner. Results: After a minimum of 1-year follow-up, no recurrent infections were diagnosed, 1 patient suffered a complication requiring expedited antibiotic spacer removal, and 1 patient expired in this cohort. Conclusions: This technique represents an effective method of providing stability of the knee and delivering adequate antibiosis in patients with knee periprosthetic joint infections in the setting of extensor mechanism disruption and severe bone loss.